AERODYNAMICS AND AEROACOUSTICS SURVEY FOR A LOW SPEED SUBSONIC JET OPERATING AT MACH 0.25 - Proença, A. R.; de almeida, O.; Self, R. H. (Revista de Engenharia Térmica, 2014)
The purpose of this work is to study and characterize, in laboratory, the aerodynamics of a free jet operating at subsonic regime and identify its acoustic signature. This study aims to analyze the fundamental role of turbulent flow structures in the total noise produced at different Mach numbers. This work is focused at low speed subsonic jets operating at Mach number 0.25. The research is done by analyzing the data obtained in experiments using Pitot tube, hot-wire anemometer and acoustic measurements. This work also describes the experimental procedures for each step of analysis, as well as the characteristics of jet noise facility. The data from measurements with Pitot tube is used to study the mean velocity profiles. The average properties are also analyzed with anemometry system, likewise used to study the turbulent intensity of eleven axial lines, ranging from the center line to the edge of the nozzle (lipline). These results are compared with the literature and is verified the accuracy of hot-wire anemometers for turbulent intensities lower than 15%. A database with the sound pressure level as a function of frequency is constructed from experiments serving as data for further numerical analysis to solve this problem.